To assess the effectiveness of Systane COMPLETE in improving meibomian gland score and in reducing symptoms of ocular dryness - Sharma, Namrata; Bari, Aafreen; Malik, Anu; Maharana, Prafulla Kumar; Shakkarwal, Chetan; Sharma, Shivam; Dasgupta, Aishwarya (Frontiers in Ophthalmology, 2025)
PurposeTo assess the effectiveness of Systane COMPLETE in reducing symptoms of ocular dryness and improving Meibomian Gland (MG) Score in subjects with mild to moderate dry eye disease (DED).MethodsA prospective, interventional, single-center, single-arm study was conducted including cases of mild to moderate DED. Participants were prescribed a topical lipid-based combination of propylene glycol (PG) and hydroxypropyl guar (HPG) (Systane® COMPLETE), administered four times daily for 30 days. Dry eye assessment parameters, Meibo score, and Ocular Surface Disease Index (OSDI) questionnaire responses were obtained before and after treatment.ResultsA total of 105 cases with mild to moderate DED were included in the study. Statistically significant improvements were observed in tear breakup time (TBUT) (p<0.0001), Schirmer’s test (p<0.0001), lipid layer thickness (LLT) (p<0.0001), tear meniscus height (TMH) (p=0.0002), non-invasive breakup time (NIBUT) (p<0.0001), OSDI (p<0.0001), upper lid meibomian gland score (p=0.02), corneal staining score (p<0.0001). The change in Meibo score was not statistically significant (p=0.19).ConclusionA lipid-based nanoemulsion of PG–HPG helps in improving the objective parameters and symptoms of DED. Additionally, it may support improved meibomian gland function.